Influence of processing conditions on manufacturing polyamide parts by ultrasonic molding. (15th May 2016) - Grabalosa, J.; Ferrer, I.; Elías-Zúñiga, A.; Ciurana, J.
Abstract: Ultrasonic molding is a new manufacturing process for producing small and micro polymeric components where the material is plasticized using vibration energy. In small parts manufacturing, replicability is usually demanded. Downscaled tensile specimens were manufactured using ultrasonic molding on polyamide pellets not only to obtain specimens, but also to investigate the influence of the processing conditions on process performance and material characterization. A modeling approach is proposed to assess the energy flow involved in the process. It was observed that 300 mg of polyamide could be plasticized and injected in less than 3 s and the results showed a relationship between the processing conditions and the final product, i.e. the higher the values of applied pressure, ultrasonic time and vibration amplitude, the more accurate and more homogeneous parts were. Moreover, the material did not suffer chemical degradation, but light variation on the molecular weight and different chain alignment along the specimen were detected. The mechanical properties measured were slightly influenced by the processing conditions and were in accordance with what would be expected for that particular material when being processed using conventional injection molding. Graphical abstract: Highlights: Polyamide small tensile specimens were successfully manufactured by ultrasonic molding and filling quality was analyzed. Higher values of ultrasonic time and applied pressure improved filling ratio and dimensional accuracy. Processing parameters slightly influenced mechanical properties, which are in accordance to the expected ones. Obtained parts does not show chemical degradation but variation on the molecular weight was observed.